Recent results from Borexino. Issue 6 (May 2016) - Testera, G; Agostin, M; Altenmüller, K; Appel, S; Bellini, G; Benziger, J; Bick, D; Bonfini, G; Bravo, D; Caccianiga, B; Calaprice, F; Caminata, A; et al.
Abstract: We review the solar neutrinos results of Borexino and the limit on the charge conservation obtained in the context of the analysis of the low energy region of the energy spectrum.